Creation of catalytically active particles from enzymes crosslinked with a natural bifunctional agent—homocysteine thiolactone. Issue 9 (September 2014) - Stroylova, Yulia Y.; Semenyuk, Pavel I.; Asriyantz, Regina A.; Gaillard, Cedric; Haertlé, Thomas; Muronetz, Vladimir I.; Mackie, Alan
ABSTRACT The current study describes an approach to creation of catalytically active particles with increased stability from enzymes by N‐homocysteinylation, a naturally presented protein modification. Enzymatic activities and properties of two globular tetrameric enzymes glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH) and lactate dehydrogenase (LDH) were studied before and after N‐homocysteinylation. Modification of these proteins concerns the accessible lysine residues and introduces an average of 2–2, 5 homocysteine residues per protein monomer. Formation of a range of aggregates was observed for both enzymes, which assemble via formation of intermolecular noncovalent bonds and by disulfide bonds. It was demonstrated that both studied enzymes retain their catalytic activities on modification and the subsequent formation of oligomeric forms. At low concentrations of homocysteine thiolactone, modification of GAPDH leads not only to prevention of spontaneous inactivation but also increases thermal stability of this enzyme on heating to 80°C. A moderate reduction of the activity of GAPDH observed in case of its crosslinking with 50‐fold excess of homocysteine thiolactone per lysine is probably caused by hindered substrate diffusion. Spherical particles of 100 nm and larger diameters were observed by transmission electron microscopy and atomic force microscope techniques after modification of GAPDH with different homocysteine thiolactone concentrations. In case of LDH, branched fibril‐like aggregates were observed under the same conditions. Interestingly, crosslinked samples of both proteins were found to have reversible thermal denaturation profiles, indicating that modification with homocysteine thiolactone stabilizes the spatial structure of these enzymes. © 2014 Wiley Periodicals, Inc. Biopolymers 101: 975–984, 2014.